2017
DOI: 10.1038/s41598-017-01764-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrin beta8 (ITGB8) activates VAV-RAC1 signaling via FAK in the acquisition of endometrial epithelial cell receptivity for blastocyst implantation

Abstract: Integrin beta8 (ITGB8) is involved in the endometrial receptivity. The blastocyst first interacts with the luminal endometrial epithelial cells during its implantation; therefore, we have investigated the signaling of ITGB8 via FAK and VAV-RAC1 in the endometrial epithelial cells. Integrin beta8 was found elevated in epithelial cells at late-pre-receptive (day4, 1600 h) and receptive (day5, 0500 h) stages of endometrial receptivity period in the mouse. Integrins downstream molecule FAK has demonstrated an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…iTGB8 is an important member of the integrin family, members of which are mediators of the interactions between cells and the matrix (34). Previous studies have revealed that iTGB8 in perivascular astrocytes plays an important role in regulating brain vessel homeostasis through modulation of TGF-β activation and expression of TGF-β-responsive genes that promote vessel differentiation and stabilization (35).…”
Section: Discussionmentioning
confidence: 99%
“…iTGB8 is an important member of the integrin family, members of which are mediators of the interactions between cells and the matrix (34). Previous studies have revealed that iTGB8 in perivascular astrocytes plays an important role in regulating brain vessel homeostasis through modulation of TGF-β activation and expression of TGF-β-responsive genes that promote vessel differentiation and stabilization (35).…”
Section: Discussionmentioning
confidence: 99%
“…Among the miRNAs differentially expressed between gestational days 12 and 15, miR-142-5p and miR-142-3p exhibited a negative expression pattern with ITGB 8, which could influence endometrial receptivity and regulate embryo attachment [41,42]. The 3′UTR region of ITGB 8 has a binding site for miR-142-3p, and this regulatory relationship has been reported in glioma [43].…”
Section: Discussionmentioning
confidence: 99%
“…Another group has shown that various integrin subunits α 1, α 4, β 1, and β 5 were known to be expressed in endometrial epithelium during the implantation window [7]. Recently, Kumar et al [32] showed that integrin β 8 activates VAV-RAC1 signaling axis via FAK to facilitate the endometrial epithelial cell receptivity for blastocyst implantation. Previously, we also reported that LIF regulates endometrial receptivity via integrins α V β 3 and α V β 5 [18].…”
Section: Discussionmentioning
confidence: 99%